Sensory characteristics and referential standards in the metaphorical description of human eyes (based on Russian, English and Spanish languages) - Kotov, Kirill A. (Journal of the Belarusian State University. Philology, 2025)
The article analysed 803 metaphorical descriptions of human eyes in Russian, English and Spanish languages. Their common and national specific features are established. Sensory characteristics of eyes (color, size, shape, etc.) as well as denotative domains (plants, animals, people, artifacts, etc.), which serve as sources of referential standards in the metaphorical descriptions of human eyes, are identified. The probable causes for frequency variations of the sensory characteristics of eyes are formulated, and factors, influencing the selection and frequency of denotative domains, are identified.